THE INFLUENCE OF BRAND IMAGE, PRICE, PROMOTION, AND DISTRIBUTION CHANNELS ON PURCHASE DECISIONS OF DOMESTICALLY PRODUCED INDUSTRIAL LED LIGHTING - Devi Laksmi; Udin Ahidin; Kasmad (PT. Jurnal Center Indonesia Publisher, 2026)
This study explores the role of brand image, price, promotion, and distribution channels in shaping consumer purchasing decisions for domestically produced industrial LED lighting products. A quantitative research approach was employed using a survey method, with data analyzed through multiple linear regression. The findings indicate that the proposed model is statistically significant, demonstrating that all marketing mix elements jointly influence purchasing decisions. Each variable also shows a positive and significant individual effect, with distribution channels emerging as the most influential factor in driving consumer decisions. This suggests that ease of access, product availability, and effective distribution play a critical role in the adoption of industrial LED products. The novelty of this research lies in empirically integrating marketing mix factors within the context of domestically manufactured LED products, an area that has received limited scholarly attention. The study offers practical implications for manufacturers, emphasizing the importance of strengthening distribution strategies and aligning pricing and promotional efforts to enhance consumer purchasing decisions